Analisis Kesalahan Berbahasa Pada Teks Ulasan Film Alive Kelas VIII SMP Shuffah Al-Jama’ah Tasikmalaya - Galih Ahmad Rivaldi; Syifa Nurlatifah; Wafa Arifa Fiqri; Ai Siti Nurjamilah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The background of this research is students’ mistakes in writing review texts based on linguistic level studies. This research analyzes the fields of phonology, morphology, semantics and syntax in the review text of the film entitled Alive. This research aims to obtain results of language analysis errors in grade 8 students at Shuffah Al-Jamaah Tasikmalaya Middle School. The research method uses analytical descriptive research. The sample selection method in this study used a simple random sampling method. The data collection method used is (1) accumulating the results of students’ review texts at school as a data source, (2) reading carefully all data sources, (3) marking and assigning classification codes to the data, (4) classifying data based on the form of error. Language use, (5) presenting and describing data based on forms of language use errors. The instrument used is data analysis. Based on the results of data analysis, the most dominant errors that emerged were errors in the field of phonology, namely the omission of phonemes. Apart from that, it is also often found in the field of morphology regarding reduplication, namely the use of the word repeat with a square sign. The deletion of phonemes and incorrect reduplication of writing occurs, which is done by students to shorten the writing of a word so that the writing process can be completed more quickly without paying attention to good and correct linguistic rules. Students need to concentrate and be more careful in the process of writing activities. Apart from that, teachers also need to provide direction in the form of knowledge and insight regarding the basics of good and correct linguistics to minimize the occurrence of language mistakes and mistakes.